English Proficiency in Jakarta and Lampung: Insights from the 2019 National Examination - Fefiyana, Fefiyana; Suryawati, Sri Suci; Nabila, Aulia; Prastiti, Khoirunnisa Candra; Silfani, Ani Nuraeni (English Education: Jurnal Tadris Bahasa Inggris, 2025)
This study examined the 2019 National Examination language scores of senior high school students in Jakarta and Lampung, Indonesia. National examinations are a cornerstone of Indonesia's education system, vital for assessing student competency and ensuring quality control. However, persistent regional disparities in these exam results are a known challenge. This research aimed to address a gap in the literature by directly comparing these language scores between the urban center of Jakarta and the more rural Lampung. The results revealed a significant performance gap, with Jakarta students consistently scoring higher. Factors such as resource availability, teacher quality, and socioeconomic status are discussed as potential contributors to this disparity. The study highlights the ongoing challenge of achieving educational equity in Indonesia and underscores the urgent need for targeted interventions to bridge these regional differences.